The effect of urban geometry on outdoor thermal comfort. Application of the UTCI index in hot and arid climates. - Sedira, Sara; Mazouz, Said (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The object of our study is to evaluate the effect of urban geometry on microclimate and outdoor thermal comfort. In this context, “the RayMan pro 2.1” software was adopted to define UTCI index applying in hot and arid climates, exactly, in the urban fabric of the Ksar of The Red Village, El Kantara in Biskra city, Algeria, to define the most efficient urban geometry in term of summer thermal comfort by studying the real impacts of the urban form on the solar control and microclimatic conditions. studying the correlation between the geometry of the street estimated by the ratio H/L, the sky view factor (SVF), its orientation and the evolution of the physical variables (Ta, MRT, Ws) and the values of UTCI index. Significant relationships were found between UTCI index, urban geometry and heat stress in outdoor environments. The results of this research have shown the effect of urban design strategies on modifying the microclimatic conditions in hot summer for outdoor spaces in hot-arid climate.